Translating Mad Cow Disease: A Case Study of Subtitling for a Television News Magazine - Kang, Ji-Hae (Meta, 2012)
This paper explores how discourse is reframed in audiovisual translation in a well-known South Korean television news magazine, PD Swuchep [PD Notebook]. The episode under consideration raised serious questions regarding the safety of US beef and the conduct of South Korean officials responsible for negotiating imported beef in the Korea-US Free Trade Agreement talks. The program, which contained sound bites of interviews in English subtitled in Korean, created uproar in the South Korean society and played a significant role in touching off many months of massive street rallies against the government for its alleged sloppy handling of the beef import negotiation talks. Based on the view that subtitling for television news is a practice of “entextualization,” the study argues that (1) different degrees of discursive transformations in the target text cumulatively work to support and exaggerate the risk of the transmission of mad cow disease as a result of eating American beef; and (2) the discursive transformation is reinforced by institutionally defined roles and procedures for target text production. The findings suggest that one of the main criteria for the selection of target text expressions may be the narrative relevance of the political slant of the translation to the story of the program. Furthermore, the narrative of the target text may not necessarily be consensually co-constructed by participants. On the contrary, it is often a product of conflict-ridden processes that are characterized by tensions and differences in power relationships among people in different roles in the media institution.